The Development Of S. oryzae L. Population And The Damage On Five Types Of Rice In The Laboratory - RAMADHANIA, RAHMI; RAMADHAN, TRIS HARIS; SARBINO, SARBINO (Jurnal Sains Mahasiswa Pertanian, 2018)
The Development Of S. oryzae L. Population And The Damage On Five Types Of Rice In The LaboratoryRahmi Ramadhania1, Tris Haris Ramadhan2, Sarbino3Â 1Agriculture; Faculty University of Tanjungpura2Agriculture; Faculty University of Tanjungpura3Agriculture; Faculty University of Tanjungpurae-mail: *rahmiramadhania96@gmail.comÂ Â ABSRTACTRice is the main food for the consumtion of Indonesian society. But, there is biological damage factor due rice weevils. Sitophilus oryzae L in rice storing. This study aims to determine the development of S. oryzae L. population and the damage due it towards five types of rice in the laboratory. The research was carried out at the Plant Pest Laboratory of Faculty of Agriculture of Tanjungpura University for about 6 months. 3 pairs adult results of propagation maintained keep on 20 grams of rice. Rice used is red rice, inpara 3 rice, ketupat rice, bangkok rice, and ketupat rice. After 7 days, adults is taken an observed appearance of imago, population averages, weight of adults and rice damage. Appearance of imago, population averages, weight of adults and rice damage highest in red rice, while the lowest in pioneer rice. The most resistance rice towards the attack and damage is pioneer rice, while the most vulnurable is brown rice. In the stages of the developmental phases of eggs, larvae, pupa, preadult and adult, red rice shows a phase of development faster than other types of rice.Key words: Damage, growth, rice type, S. oryzae L.